2020
DOI: 10.1080/15592294.2019.1709267
|View full text |Cite
|
Sign up to set email alerts
|

Promoter aberrant methylation status ofADRA1Ais associated with hepatocellular carcinoma

Abstract: The aim of our study was to explore the relationship between the methylation status of the alpha-1A adrenergic receptor (ADRA1A) gene and hepatocellular carcinoma (HCC). We combined our inhouse data-set with the Cancer Genome Atlas (TCGA) data-set to screen and identify the methylation status and expression of adrenergic receptor (AR) genes in HCC. Immunohistochemistry and western blot were performed to assess the expression of ADRA1A in HCC cell lines and tissues. We further evaluated the methylation levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Moreover, TOP2A has also been a valuable prognostic marker for tumor advancements, recurrences, and predictors of poor survival in a variety of cancers, such as breast, ovarian, colon, and small cell lung cancer ( 29 ). ADRA1A encodes the alpha-1 adrenergic receptor subtype with catecholamines ligands ( 31 ), which is located on chromosome 8p ( 32 ). ADRA1A can stimulate the sympathetic nervous system to compete with some functions ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TOP2A has also been a valuable prognostic marker for tumor advancements, recurrences, and predictors of poor survival in a variety of cancers, such as breast, ovarian, colon, and small cell lung cancer ( 29 ). ADRA1A encodes the alpha-1 adrenergic receptor subtype with catecholamines ligands ( 31 ), which is located on chromosome 8p ( 32 ). ADRA1A can stimulate the sympathetic nervous system to compete with some functions ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer develops through the accumulation of genetic and epigenetic aberrations, and epigenetic changes are strongly associated with the development of HCC. As reported, many genes such as ADRAIA, ACADS, UBE2Q1, and ZCCH13 have been found to have aberrant methylation status in HCC (Hu et al 2017;Chen et al 2019;Li et al 2019;Chen et al 2020). Abnormal methylation of genes may be promising biomarkers to timely and accurately distinguish patients with HBV-associated HCC from patients with CHB.…”
Section: Discussionmentioning
confidence: 83%
“…Like the results in this study, the level of methylation at different sites has very different effects on the prognosis of patients. In recent years, studies have shown that methylation of the RIZ1 gene promoter region in HCC tissues is associated with postoperative tumor recurrence, which may be the reason for the poor prognosis of patients with RIZ1 gene methylation positive in HCC tissues ( 21 ); Similarly, another study also showed that Compared with normal tissues, the methylation level of the ADRA1A promoter region in the tumor tissues of HCC patients was significantly increased, the mRNA and protein levels of ADRA1A were decreased, and DNA methyltransferase inhibitors could increase the mRNA expression of ADRA1A ( 22 ). It shows that ADRA1A gene hypermethylation may be involved in the occurrence of HCC.…”
Section: Discussionmentioning
confidence: 98%